Physicochemical properties of germinated brown rice (Oryza sativa L.) starch - Musa, Siti Nor Asma; Imam, Mustapha Umar; Ismail, Maznah (Academic Journals, 2011)
Physicochemical properties of white rice (WR), brown rice (BR) and germinated brown rice (GBR) starches from a mixed variety of MR219 and MR220, commonly consumed Malaysian varieties, were compared in this study. The granular size of the starch particles, measured using scanning electron microscope (SEM), varied from 2 to 8 μm for all starches and appeared in polyhyedral shapes. Amylose content in WR, BR and GBR as analysed using colorimetric method was found to be 25.77, 23.83 and 21.78%, respectively. The amylose content of GBR was significantly lower than that of WR or BR. Results also show that germination affected gelatinization and pasting properties. This study has profound implications for future studies on functional properties of GBR and may help us understand what role changes in physicochemical properties, brought about by germination, play in determining functional effects.